INHIBITION OF PACLITAXEL AGAINST NEUROGLIOMA CELLS U251 GROWTH AND ITS MECHANISM - Xin, ShiMeng; Yu, Fang; Yang, ChunYan; Hao, Xia (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Glioma is the most common primary tumor of the central nervous system, and accounted for about 70% of primary tumors. Materials and Methods: In the study, antitumour activity and mechanism of paclitaxel was investigated. Different concentrations of paclitaxel (200, 300, 400 μmol/L) was treated in neuroglioma cellsU251. Results: Paclitaxel significantly inhibited neuroglioma cells growth, and promoted its apoptosis. Paclitaxel can block tumour cells in the G2/M phase. In addition, apoptosis-related genes caspase-3 and bax expressions were increased after paclitaxel treatment. Conclusion: Our work indicated that paclitaxel displayed strong anti-tumour activity.